Thematic village Zalesie Royal - Dombrowicz, Maria; Gotowski, Rafał (Journal of Education, Health and Sport, 2016)
Zalesie Królewskie is a village located in the district lay in the municipality of Swiekatowo. It is a town with well-preserved heritage Borowiakow Tucholskich. This heritage is rich and focused around the values of material culture, but also immaterial. People who live here have many features in common with neighboring Kociewiacy and Kashubian, but also have their own unique ethnographic, which is attractive for tourism.